A simple vaporous probe with atomic-scale sensitivity to structural ordering and orientation of molecular assembly. Issue 29 (19th June 2019) - Cheng, Han-Wen; Wu, Zhi-Peng; Yan, Shan; Li, Jing; Shan, Shiyao; Wang, Lichang; Porter, Marc D.; Zhong, Chuan-Jian
Abstract : We report a simple combination of vaporous probe and quartz crystal microbalance with atomic-scale sensitivity to interfacial ordering and orientation. Abstract : Understanding the structural ordering and orientation of interfacial molecular assemblies requires an insight into the penetration depth of the probe molecules which determines the interfacial reactivity. In contrast to the conventional liquid probe-based contact angle measurement in which penetration depth is complicated by the liquid cohesive interaction, we report here a new approach that features a simple combination of vaporous hexane, which involves only van der Waals interaction, and quartz crystal microbalance operated at the third harmonic resonance, which is sensitive to sub-monolayer (0.2%) adsorption. Using this combination, we demonstrated the ability of probing the structural ordering and orientation of the self-assembled monolayers with a sensitivity from penetrating the top portion of the monolayers to interacting with the very top atomic structure at the interface. The determination of the dependence of the adsorption energy of vaporous hexane on the penetration depth in the molecular assembly allowed us to further reveal the atomic-scale origin of the odd–even oscillation, which is also substantiated by density functional theory calculations. The findings have broader implications for designing interfacial reactivities of molecular assemblies with atomic-scale depth precision.